Learning through letzhop.com : Interaction design concerns in supporting usability attributes - Jamaludin, Zulikha; Abdul Rahman, M.G.; Konchong, H.A.; Talib, R. (International Association of Technology, Education and Development (IATED), 2008)
Learning alone does not counts as much as doing. LetzHop™, at Letzhop.com portal, through its ten edutainment modules provide the means for learning by doing. This paper focus on the design and development of Letzhop’s learning modules and its interaction design (IxD). The learning modules are game-based, developed separately and integrated into a learning portal whilst maintaining the emphasis on the concept of learning by doing. The portal focuses on its interleaved modules, which consist of diverse interactive online events and activities. The activities are structured as a combination of rich media contents infused with interactive choices made by the user via the Letzhop’s universal IxD. The functionality testing was performed separately on each and every modules. This paper also lays emphasis on a usability testing carried out on Letzhop.com aiming at testing its four dimensions of IxD attributes namely, usefulness, ease of use, ease of learning, and subjective satisfaction. The result gathered from the evaluation shows that users associated Letzhop with positive attributes, which in turns suggests that our way of designing, developing, and integrating the IxD aspects of the modules are viable.